Childbirth, morbidity, sickness absence and disability pension: a population-based longitudinal cohort study in Sweden - Wang, Mo (BMJ Open, 2020)
OBJECTIVE: To investigate associations of morbidity with subsequent sickness absence (SA) and disability pension (DP) among initially nulliparous women with no, one or several childbirths during follow-up. DESIGN: Longitudinal register-based cohort study. SETTING: Sweden. PARTICIPANTS: Nulliparous women, aged 18 to 39 years and living in Sweden on 31 December 2004 and the three preceding years (n=492 504). OUTCOME MEASURES: Annual mean DP and SA days (in SA spells >14 days) in the 3 years before and after inclusion date in 2005. METHODS: Women were categorised into three groups: no childbirth in 2005 nor during the follow-up, first childbirth in 2005 but not during follow-up, and having first childbirth in 2005 and at least one more during follow-up. Microdata were obtained for 3 years before and 3 years after inclusion regarding SA, DP, mortality and morbidity (ie, hospitalisation and specialised outpatient healthcare, also excluding healthcare for pregnancy, childbirth and puerperium). HRs and 95% CIs for SA and DP in year 2 and 3 after childbirth were estimated by Cox regression; excluding those on DP at inclusion. RESULTS: After controlling for study participants’ prior morbidity and sociodemographic characteristics, women with one childbirth had a lower risk of SA and DP than those who remained nulliparous, while women with more than one childbirth had the lowest DP risk. Morbidity after inclusion that was not related to pregnancy, childbirth or the puerperium was associated with a higher risk of future SA and DP, regardless of childbirth group. Furthermore, morbidity both before and after childbirth showed a strong association with SA and DP (HR range: 2.54 to 13.12). CONCLUSION: We found a strong positive association between morbidity and both SA and DP among women, regardless of childbirth status. Those who gave birth had lower future SA and DP risk than those who did not.